2022
DOI: 10.3390/curroncol29110637
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits Are Related to Phase Angle in Male Patients with Non-Small-Cell Lung Cancer

Abstract: Introduction: Lung cancer constitutes the most common cause of cancer death. Phase angle (PhA) has been related to lung cancer prognosis, which implies that the identification of dietary or other factors that could predict or modify PhA may have beneficial effects. Νutritional interventions have been linked with positive changes in PhA in certain types of cancer. Aim: The present study aimed to investigate the relationships between dietary habits/nutrition and PhA in NSCLC patients. Methods: The sample consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…The causal association of chemotherapy with PhA might be complex. Beyond direct damage to cells by cytostatic drugs, reduced physical activity, altered dietary habits and poor nutritional status as a result of chemotherapy could also play a role with regard to the decreased PhA after chemotherapy 40 . With respect to fatigue, however, our mediation analysis does not suggest a role of PhA in the causal pathway of the chemotherapy effects on fatigue.…”
Section: Discussioncontrasting
confidence: 60%
“…The causal association of chemotherapy with PhA might be complex. Beyond direct damage to cells by cytostatic drugs, reduced physical activity, altered dietary habits and poor nutritional status as a result of chemotherapy could also play a role with regard to the decreased PhA after chemotherapy 40 . With respect to fatigue, however, our mediation analysis does not suggest a role of PhA in the causal pathway of the chemotherapy effects on fatigue.…”
Section: Discussioncontrasting
confidence: 60%
“…This systematic review includes several types of studies: five prospective studies [ 35 39 ], three observational studies [ 40 42 ], two retrospective studies [ 34 , 43 ] and one cross-sectional study [ 44 ]. Shi et al showed the highest number of patients involved (804).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining selected scientific papers included 30 to 204 patients. Five studies included both males and females, six studies included males only [ 36 , 38 , 40 42 , 44 ]. However, in two studies [ 36 , 37 ], we do not know if the percentages of women and men present in the study referred to LC patients or patients with other kind of cancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is possible that the total diet and/or dietary protein may be important in addressing this issue, since sarcopenia often co-exists with osteoporosis (osteosarcopenia) [ 70 ]. In this case, animal protein may be a key factor for modifying body composition and sarcopenia, such as in the case of cancer, which is also related to sarcopenia [ 71 , 72 ]. In addition, inflammatory indices, such as platelet activating factor, are related to OF [ 73 ], and an antioxidant-rich diet and/or fatty acid profile may lessen its deleterious actions [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%